Impact of Bedaquiline on Multidrug-Resistant Tuberculosis Treatment to Mother and Baby: An Incidental Case - Tutik Kusmiati1 , Faradila Nur Aini2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Bedaquiline is a new drug which is recommended by World Health Organization (WHO) forindividual regiment drug resistant-tuberculosis (DR-TB). The presence of regiment DR-TB in the bloodis long enough with T1/2 5-6 months, that is why bedaquiline is given on six months. Bedaquiline is notrecommended for pregnant women because there is no data related to safety. The author will report anincidental pregnant female on bedaquiline treatment.Case presentation: A 24-year-old woman with multidrug resistant tuberculosis (MDR TB) on individualregiment bedaquiline had incidental pregnancy at the 6th month treatment. In the beginning, the patientused bedaquiline because of the intolerance of second-line injectable drug. Bedaquiline regiment was usedfor 24th week. Pregnancy occured at the 6th month treatment. The patient continued the pregnancy and theMDR TB treatment was continued without bedaquiline. Nausea and vomiting were getting worse. Pretermlabour occured in 33/34 weeks by cesarean section. The baby had severe asphyxia, used continuous positiveairway pressure (CPAP), treated in NICU, had low weight but there was no disability. After several days oftreatment, the condition of baby was improving and was able to outpatient.Conclusion: The preterm labour, low birth weight, and neonatal emergency occured in a pregnant womanwith MDR TB on individual regiment bedaquiline. Mother and baby can survive. More case and researchdata are needed on the safety of bedaquiline during pregnancy.